Conduct analysis of hospitality organisations - Kulbert, Gábor; Ionescu, Astrid (Észak-magyarországi Stratégiai Füzetek, 2024)
Tourism and the hospitality industry that organically joins it are of decisive economic importance worldwide, about 10% of the Hungarian working population works in this sector. The aim of our research is to present the structure of the organizations in the sector, focusing on the different perspectives of managers and subordinates in relation to decision-making, responsibility issues, subordination relations and sustainability. Decision making during operation is important for the successful operation of organizations, so it is necessary for managers to understand the factors that influence the decisions of their subordinates. Although decision-making is always the responsibility of the leader, in an ever-changing, evolving sector that requires quick response is a decisive success factor. Data was collected by conducting in-depth interviews on site in the summer of 2024, during which we interviewed the manager of the catering establishments separately and an employee of our choice.